Early diagnosis and monitoring of nitrogen nutrition stress in tomato leaves using electrical impedance spectroscopy - Meiqing, Li; Jinyang, Li; Xinhua, Wei; Wenjing, Zhu (International Journal of Agricultural and Biological Engineering, 2017)
Abstract: Nitrogen (N) is a life element for crop growth. In tomato growth and development, N stress often occurs and degrades crop yield and quality. Superfluous N can noticeably increase the nitrate content, which can be degraded into strong carcinogenic substance- nitrite. An accurate and timely monitoring and diagnosis of nutrition during crop growth is premise to realize a precise nutrient management. Crop N monitoring methods have been developed to improve N fertilizer management, and most of them are based on leaf or canopy optical property measurements. Although many optical/spectral plant N sensors have already commercialized for production use, low accuracy for phosphorus (P) and potassium (K) detection and diagnosis remains an important drawback of these methods. To explore the potential of N diagnosis by electrical impedance and perform study for nutrition status of plant NPK meanwhile by the electrical impedance, it is necessary that evaluate the N nutrition level by leaf impedance spectroscopy. Electrical impedance was applied to determine the physiological and nutritional status of plant tissues, but few studies related to plant N contents have been reported. The objective of this study was to evaluate the N nutrition level by leaf impedance spectroscopy and realize the early diagnosis and monitoring of N nutrition stress in tomato. Five sets of tomato plant samples with different N contents were cultivated in a Venlo greenhouse. N content of leaves was determined, and electrical impedance data were recorded in a frequency range of 1 Hz to 1 MHz. The obtained impedance data were analyzed using an equivalent circuit model for cellular tissues. The variation of equivalent parameters along with N content was analyzed, and the sensitive impedance spectroscopy characteristics of N nutrition level were extracted. Furthermore, the effect of moisture content on impedance measurement was discussed and the prediction model for N content was developed. Results showed that electrical impedance can be conveniently applied to early diagnosis and monitoring for tomato N nutrition stress.Keywords: electrical impedance spectroscopy, nitrogen stress, tomato (Solanum lycopersicum) leaves, nitrogen nutrition, diagnosis, monitoring, nondestructive detectionDOI: 10.3965/j.ijabe.20171003.3188Citation: Li M Q, Li J Y, Wei X H, Zhu W J. Early diagnosis and monitoring of nitrogen nutrition stress in tomato leaves using electrical impedance spectroscopy. Int J Agric & Biol Eng, 2017; 10(3): 194–205.